Preclinical Efficacy and Clinical Feasibility of a Novel Aerosol-Exposure Protection Mask for Esophagogastroduodenoscopy - Mai Ego Makiguchi; Seiichiro Abe; Yutaka Okagawa; Satoru Nonaka; Haruhisa Suzuki; Shigetaka Yoshinaga; Ichiro Oda; Okamoto Ryuta; Yutaka Saito (Korean Society of Gastrointestinal Endoscopy, 2022)
Background/Aims This study aimed to assess the efficacy of a novel aerosol-exposure protection (AP) mask in preventing coronavirus disease in healthcare professionals during upper gastrointestinal endoscopy and to evaluate its clinical feasibility. Methods In Study 1, three healthy volunteers volitionally coughed with and without the AP mask in a cleanroom. Microparticles were visualized and counted with a specific measurement system and compared with and without the AP mask. In Study 2, 30 patients underwent endoscopic resection with the AP mask covering the face, and the SpO2 was measured throughout the procedure. Results In Study 1, the median number of microparticles in volunteers 1, 2, and 3 with and without the AP mask was 8.5 and 110.0, 7.0 and 51.5, and 8.0 and 95.0, respectively (p<0.01). Using the AP mask, microparticles were reduced by approximately 92%. The median distances of microparticle scattering without the AP mask were 60, 0, and 68 in volunteers 1, 2, and 3, respectively. In Study 2, the mean SpO2 was 96.3%, and desaturation occurred in three patients. Conclusion The AP mask could provide protection from aerosol exposure and can be safely used for endoscopy in clinical practice.